BARRIERS FACED BY WOMEN IN LEADERSHIP ROLES IN CBSE SCHOOLS OF VADODARA CITY - Rajawat, Deepika; Pathan, Reshma Papasaheb; Baral, Satyajit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Women, who make up half of the global population, continue to face inequality in various sectors, both governmental and non-governmental, especially when it comes to leadership roles. Achieving equality for women in top corporate positions is often a long and challenging process, requiring the commitment of the entire organization, particularly its leadership. According to United Nations reports, women constitute half of the world’s population and perform two-thirds of the world’s work but receive only one-tenth of its income and own less than one percent of its property. Over 40% of the global labor force is made up of women, yet they remain underrepresented in leadership roles. In developing countries, especially in rural areas, women are responsible for producing more than 55% of the food. Despite studies showing that women are successful business owners and managers, they represent only 16% at junior management levels, 4% at middle and senior levels, and just 1% in leadership positions. This paper, based on secondary data, explores the challenges women face in leadership and management in India.